The Effect of Family Environment on Student Learning Achievement: A Review of the Literature in Indonesia - Mohamad Ardin Suwandi; Heinrich Rakuasa; Philia Christi Latue (Journal of Loomingulisus ja Innovatsioon, 2024)
Contains a detailed summary of the research conducted and written in 1 This research examines the influence of family environment on student learning achievement in Indonesia. By analyzing existing literature, this research identifies key factors such as parental involvement, socioeconomic status and family dynamics that influence student learning outcomes. The methods used include quantitative, qualitative and mixed research to provide a comprehensive understanding of this relationship. Findings show that a supportive family environment contributes positively to students' academic achievement and educational aspirations. This research provides important implications for parents, educators and policy makers in creating an environment conducive to learning.